2011
DOI: 10.1016/j.bmc.2011.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antileishmanial in vitro activity of new series of chalcones-like compounds: A molecular hybridization approach

Abstract: The chalcone-like series 1a-1g was efficiently synthesized from Morita-Baylis-Hillman reaction (52-74% yields). Compounds 1a-1g were designed by molecular hybridization based on the anti-inflammatory drug methyl salicylate (3) and the antileishmanial moiety of the Morita-Baylis-Hillman adducts 2a-2g. The 1a-1g compounds were much more actives than precursor series 2a-2g, for example, IC(50)=7.65 μM on Leishmania amazonensis and 10.14 μM on Leishmania chagasi (compound 1c) when compared to IC(50)=50.08 μM on L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 51 publications
1
16
0
5
Order By: Relevance
“…The sensitivity of promastigotes to HNAB, trivalent (potassium antimonyl tartrate trihydrate) and pentavalent antimony (meglumine antimoniate) was evaluated as described by Barbosa et al (2011). Each experiment was performed in duplicate and repeated at least 3 times.…”
Section: Promastigote Sensitivity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of promastigotes to HNAB, trivalent (potassium antimonyl tartrate trihydrate) and pentavalent antimony (meglumine antimoniate) was evaluated as described by Barbosa et al (2011). Each experiment was performed in duplicate and repeated at least 3 times.…”
Section: Promastigote Sensitivity Assaymentioning
confidence: 99%
“…These molecules presented anti-parasitic activity against amastigotes and promastigotes of Leishmania (De Souza et al 2007;Barbosa et al 2009;Silva et al 2011). Among the compounds evaluated for anti-leishmanial activity, HNAB, which was designed based on the medicinal chemistry strategy of molecular hybridization between the methyl salicylate and an adduct that was derived from ortho-nitrobenzaldehyde, was the most active against Leishmania (Leishmania) amazonensis and L. (L.) infantum/chagasi (Barbosa et al 2011). 1) and 6 similar adducts.…”
mentioning
confidence: 99%
“…34 The toxic side effects of anti-leishmanial medications used for treatment and the development of resistance of the parasite to these medications have led to studies related to definition and formulation of new molecules to date. 37 Different studies have been completed; [12][13][14][15][16][17][18] from a study showing the anti-leishmanial activity of ethanol extracts from Allium sativa (garlic) and Azadirachta indica (Neem), locally used for treatment of Cutaneous leishmaniasis in the Sudan, had no significant difference when compared to pentostam, 16 to studies emphasizing that the anti-leishmanial efficacy on promatigotes and amastigotes of Leishmania tropica was higher compared to two antibiotics in the macrolid group of azithromycin and clarithromycin. 38 The AL-EO presented in this study can be considered for use as an antileishmanial.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Globally and in Turkey, it has been reported that resistance has developed to the primary medication for treatment of CL and VL of five valuable antimony species, sodium stibogluconate (Pentostam®) and megluminantiamoniate (Glucantime®). [12][13][14][15][16] Due to the lack of an effective prophylactic against the disease, the toxic effects of currently-used medications and the increasing resistance to these medications, the necessity for discovery and development of new therapeutic agents has been reported. 11,17,18 Trichomoniosis is a common infection everywhere in the world and the infection rates are reported to show great variations from country to country and society to society.…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca bu ilaçların çoğunun nefrotoksik, hepatotoksik ve teratojenik etkiler başta olmak üzere ciddi yan etkileri bulunmaktadır [3,9,10] . Dünyada ve Türkiye'de KL ve VL'in tedavisinde birincil ilaç olarak kullanılan beş değerli antimon türevleri, sodyum stiboglukonat (Pentostam®) ve megluminantimoniat (Glucantime®) 1940 yılında geliştirilmiş, ancak bu ilaçlara karşı direnç geliştiği, araştırıcılar tarafından bildirilmiştir [6,[11][12][13][14] .…”
Section: Hidrazon Yapısındaki On Farklı Bileşiğin Antileishmanialunclassified